PERAN LITERASI KEUANGAN DALAM MEMODERASI PENGARUH BIAS PRILAKU KEUANGAN TERHADAP INVESTASI (STUDI PADA INVESTOR SAHAM SULAWESI TENGGARA - Marliati Marliati; Sujono Sujono; Salma Saleh (Pascasarjana Universitas Halu Oleo, 2022)
The role of Financial Literacy in Moderating the influence of financial behavior bias on investment (Studies on Southeast Sulawesi Capital Market Investors. Thesis. Management Science Study Program, Postgraduate, Halu Oleo University. The purpose of this study is to explain and examine the effect of Financial Behavior Bias consisting of 6 indicators, namely Overconvidence, disposition effect, herding, risk aversion, representaveness and anchoring on investment decisions and the role of Financial Literacy in moderating the effect of financial behavior bias on investment. The research design used is quantitative research. The data used are primary data and analyzed using SPSS software version 25. The sampling technique is using the Slovin equation. And the sample in this study was 265 IDX stock investors representing Southeast Sulawesi. The results of the study show that the financial behavior bias which consists of indicators of overconvidence, representaveness and anchoring has a positive and significant effect on investment, but differs from the indicators of disposition effect, herding, and risk aversion which has a positive and insignificant effect on investment decisions. Furthermore, financial behavior bias with indicators of Overconvidence, disposition effect, risk aversion, representaveness and anchoring moderated by Financial Literacy is not significant on investment decisions, but herding indicators have a significant effect on investment decisions but in a negative direction.